Clinical Judgment: A Critical Appraisal
XXVI, 279 p.
Keywords: Over a period of a year, the symposium on clinical judgment has taken shape as a volume devoted to the analysis of how knowledge claims are framed in medicine and how choices of treatment are made. We hope it will afford the reader, whether layman, physician or philosopher, a useful perspective on the process of knowing what occurs in medicine; and that the results of the dis cussions at the Fifth Symposium on Philosophy and Medicine will lead to a better understanding of how philosophy and medicine can usefully challenge each other. As the interchange between physicians, philosophers, nurses and psychologists recorded in the major papers, the commentaries and the round table discussion shows, these issues are truly interdisciplinary. In particular, they have shown that members of the health care professions have much to learn about themselves from philosophers as well as much of interest to engage philosophers. By making the structure of medical reasoning more apparent to its users, philosophers can show health care practitioners how better to master clinical judgment and how better to focus it towards the goods and values medicine wishes to pursue. Becoming clearer about the process of knowing can in short teach us how to know better and how to learn more efficiently. The result can be more than (though it surely would be enough!) a powerful intellectual insight into a major cultural endeavor, medicine.